Cyber X UMPSA team wins Astro-NACSA Coding Challenge 2024 (ANCC2024) - Naqiah, Puaad (UMPSA, 2024)
PUTRAJAYA, 2 August 2024 – UMPSA's Cyber X team made Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) proud by winning the Astro-NACSA Coding Challenge 2024 (ANCC2024).